SISTEM AKAD MUDHARABAH TERHADAP TANGKAPAN IKAN LAUT UNIT KATROL DI DUSUN SELATAN DESA TLESAH KECAMATAN TLANAKAN KABUPATEN PAMEKASAN - Sitti Kholifah; Fawaid, Akh. (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2022)
Fishermen in Dusun Selatan, Tlesah Village, Tlanakan District use a pulley unit catching system. However, the marine fishing results agreement contract is not clear. Thus, it is possible to contract the fish catch agreement not in accordance with Islamic law. Through this research, the researcher wants to know the problems faced by fishermen. Especially in terms of catch contracts. From the above problems, the researcher directs fishermen to use the Mudharabah contract system. So that the contract is clear and in accordance with Islamic law. The purpose of this research is to provide education to fishermen about the importance of a contract that is in accordance with Islamic law so that the results obtained are halal. To explore the above problems, descriptive qualitative research methods are used. With the target of fishermen, crew members and community leaders. The results showed that the low understanding of fishermen about the contract system in Islam. So through this research there is education that fishermen get about the contract that is in accordance with Islamic law.